Cytotoxic Effects of Plant Bioactive Compounds on T47d Breast Cancer Cells Line: A Review - Firmansyah, Tio; Saraswati, Utami; Ilham, Kurniadi; Jannatan, Robby; maliza, rita (Universitas Muhammadiyah Surakarta, 2024)
The continuous cell line known as T47D cells originates from the isolation of epithelial cells from the ductal breast tissue of a 54-year-old woman with metastatic breast cancer. Numerous plant species have been employed in alternative anti-breast cancer therapy, showing advancements in recent years. The aim of this systematic review is to assess the potential bioactive compounds from herbal plant extracts and analyze the effects of herbal plants on T47D breast cancer cells. This research employs a systematic approach to gather articles, encompassing related research questions, chosen databases, keyword selection, inclusion and exclusion criteria, as well as outcomes and conclusions regarding the collected articles. From the reviewed articles, several plants exhibit anti-breast cancer activity on T47D cell lines, namely Calamintha incana, Sterculia quadrifida, Psidium guajava, Uncaria nervosa, Syzygium aqueum, Capsicum annum, Bauhinia scandens, Lansium domesticum, and Garcinia cowa due to their content of bioactive compounds such as triterpenoids, alkaloids, phenolics, flavonoids, saponins, and tannins. These bioactive compounds from the plants exert significant influence on cell cycle, proliferation, fatty acid synthesis, and apoptosis of cancer cells.